Bilateral occipital calcification, epilepsy and coeliac disease: clinical and neuroimaging features of a new syndrome. Issue 8 (August 1993) - Magaudda, A; Dalla Bernardina, B; De Marco, P; Sfaello, Z; Longo, M; Colamaria, V; Daniele, O; Tortorella, G; Tata, M A; Di Perri, R
Abstract : Twenty patients affected by bilateral occipital cortical-subcortical calcification (BOC) are described, 19 (95%) had epilepsy. In 8 of 16 cases studied, intestinal biopsy revealed coeliac disease. Fourteen patients had occipital partial epilepsy with a relatively benign outcome, while 4 patients were affected by a severe form of epilepsy, with very frequent, drug-resistant, generalised and partial seizures with mental deterioration. One patient had a single episode of convulsive status epilepticus at four months of age. The neurological examination was normal in all patients. CT showed flocculo-nodular, cortico-subcortical BOC, without enhancement and without lobar or hemispheric atrophy. MRI was normal. The clinical and neuroimaging features of these patients are different therefore from those with the Sturge-Weber Syndrome. The study confirms a high prevalence of coliac disease in patients with BOC, but the relationship between these two pathologies still needs to be clarified.